Barriers to rewilding on Sussex farmland : socio-psychological implications of rewilding on farmers’ Sense of Place - Reboah, Claire (SLU/Dept. of Urban and Rural Development, 2019)
In the wake of the Brexit referendum and the UK’s planned subsequent departure from the EU’s Common Agricultural Policy, rewilding as a land management strategy is gaining significant attention. Despite the ecological and potentially economic advantages attached to rewilding, a great proportion of the farming community is still reluctant to adopt this approach on their land.